Stres dan kejadian premenstrual syndrome pada mahasiswi pondok pesantren Surya Global - Akifah Fatimah; Yayi Suryo Prabandari; Ova Emilia (Berita Kedokteran Masyarakat (BKM), 2016)
Stress and premenstrual syndrome events in female college students in boarding schoolsPurposeThis study aimed to determine the correlation between stress and premenstrual syndrome events in female college students who live in Islamic boarding schools.MethodThis study used a cross-sectional design. Respondents were female college students who live in boarding schools and met inclusion criteria as a respondent. Data collection technique was simple random sampling.ResultsThere were correlations between stress and premenstrual syndrome, and the external variable which was related with premenstrual syndrome was age of menarche. Prevalence of female college students who experienced stress was 34.9% and prevalence of premenstrual syndrome was 32.8%. Severe symptoms experienced by respondents were physical symptoms (22.3%) such as breast tenderness, headache, joint or muscle pain, bloating, weight gain, fatigue or weakness (21.6%), and decreased interest of doing activities at home/dorm (18.1%).ConclusionFemale college students who experienced stress have more potential to experience premenstrual syndrome than female college students who did not experience stress.